Pengembangan Elektronik Lembar Kerja Peserta Didik (e-LKPD) Pada Mata Pelajaran Informatika Kelas VII SMP - Ridhoni, Rahmi; Zen, Zelhendri (Jurnal Family Education, 2023)
The background for conducting the research was due to the lack of teaching materials for Informatics class VII in junior high school. The lack of teaching materials is due to the fact that Informatics is a new subject in the Independent Curriculum. This lack of teaching materials resulted in a lot of student learning outcomes under the KKTP. The research was conducted using Research & Development (R&D) development research with the ADDIE development model. Data collection instruments in this study used validation sheets, student response questionnaires, and pre-test post-test questions. Based on the results of the media validation assessment conducted by experts in the media field I obtained a value of 3.58 which means very valid. From experts in the field of media II, a value of 3.87 is obtained, which means it is very valid. For validation from material experts, a value of 3.80 is obtained, which means it is very valid. Product practicality test results obtained a value of 3.72 which means very practical. The effectiveness test shows tcount>ttable so that there is a significant difference between the pre-test and post-test scores. It can be concluded that this E-LKPD teaching material product is effective and can be used.